Curiosity in Online Video Concept Learning and Short-Term Outcomes in Blended Medical Education - Ho, Cheng-Maw; Yeh, Chi-Chuan; Wang, Jann-Yuan; Hu, Rey-Heng; Lee, Po-Huang (Frontiers in Medicine, 2021)
Background A student’s level of curiosity in a subject after learning about it through online videos has not been addressed well in the medical education field. The purpose of this study, therefore, was to investigate online learning’s effect on the stimulation of curiosity and short-term learning outcomes in a blended framework of precision medical education. Methods A mixed-methods research design was used. During the 2020 academic year, all fifth-year medical students who, prior to class, viewed 6 video clips that presented 6 core concepts were invited to complete a survey and self-reflection on their learning process to assess their level of curiosity in each concept. For each group of medical students, teaching assistants helped collect anonymous survey data and summative assessment scores representing the students’ learning outcomes. Video-viewing patterns, attained through an action log transformation, were also coded for analysis. Mann–Whitney U and Kruskal–Wallis tests were employed to compare differences between groups, and multiple linear regression was used to select the factors affecting learning outcomes. Qualitative data were content-coded through a descriptive approach using thematic analysis. Results Of 142 medical students, 136 watched the online videos, 124 responded to the questionnaires, and 92 provided comments. Students’ curiosity levels after learning about each concept through online videos significantly correlated with the degree to which a concept was learned. Medical students spent a median of 1.6 hours online, and pause frequency correlated with curiosity in certain concepts. Aroused curiosity was associated with short-term learning outcomes in inconsistent effect sizes and directions. Students’ feedback revealed various dimensions of curiosity, including novelty acknowledgment, recognition of an information gap, and information-seeking requests. Conclusions Curiosity can be induced through online video learning platforms and has a role in short-term learning outcomes in medical education.